2023
DOI: 10.1038/s41467-023-38139-8
|View full text |Cite
|
Sign up to set email alerts
|

Crystal orientation fabric anisotropy causes directional hardening of the Northeast Greenland Ice Stream

Abstract: The dynamic mass loss of ice sheets constitutes one of the biggest uncertainties in projections of ice-sheet evolution. One central, understudied aspect of ice flow is how the bulk orientation of the crystal orientation fabric translates to the mechanical anisotropy of ice. Here we show the spatial distribution of the depth-averaged horizontal anisotropy and corresponding directional flow-enhancement factors covering a large area of the Northeast Greenland Ice Stream onset. Our results are based on airborne an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…7) but shifted slightly upwards. This could be related to the different boundary conditions (temperature, elevation) at the drill sites, the impact of extensional deformation and high strain inside NEGIS and the hard shearing in flow direction (Westhoff et al, 2021;Stoll et al, 2021a;Gerber et al, 2023), and the strong dynamic recrystallisation observed at EGRIP (Stoll et al, ). However, the grain size evolution within both cores is still comparable, and the fast-flowing ice within NEGIS does not (yet) intensely affect the grain size in the upper 2121 m (∼ 80 % of ice sheet thickness).…”
Section: Grain Size Evolutionmentioning
confidence: 99%
“…7) but shifted slightly upwards. This could be related to the different boundary conditions (temperature, elevation) at the drill sites, the impact of extensional deformation and high strain inside NEGIS and the hard shearing in flow direction (Westhoff et al, 2021;Stoll et al, 2021a;Gerber et al, 2023), and the strong dynamic recrystallisation observed at EGRIP (Stoll et al, ). However, the grain size evolution within both cores is still comparable, and the fast-flowing ice within NEGIS does not (yet) intensely affect the grain size in the upper 2121 m (∼ 80 % of ice sheet thickness).…”
Section: Grain Size Evolutionmentioning
confidence: 99%
“…However, the geometry of the ice stream, the position of its shear margins, and the origin of NEGIS itself are still not fully understood 21 , 49 – 54 . Progress in this field is expected from analyzing the EastGRIP ice core 55 , 56 , GPS measurements 46 , 57 , an extensive grid of RES profiles flown over NEGIS 58 , 59 , ground-based phase sensitive RES (pRES) measurements 60 , 61 , and modelling 62 – 64 .…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we estimated the upstream ice deformation with a simple flow line model of ice dynamics combined with satellite data, in contrast to other work which couples fabric evolution to an ice-sheet simulation (Gerber et al, 2023). In particular, we have a vertically invariant deformation over the depth examined (although the deformation experienced by an ice parcel moving through the ice stream does of course change).…”
Section: Predicting Fabrics In Nature: Future Work In Ice and Other P...mentioning
confidence: 99%